Highly conductive, high-strength metallized carbon nanotube film and preparation method thereof
By introducing a palladium transition layer onto the carbon nanotube film and forming a copper layer, the problem of insufficient interface bonding force between the carbon nanotube layer and the copper layer in the prior art is solved, and a high-conductive and high-strength metallized carbon nanotube film is realized.
Patent Information
- Application Number
- CN202211656286.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The existing preparation methods for metallized carbon nanotube films have problems of insufficient conductivity and mechanical strength, especially when the interface bonding force between the carbon nanotube layer and the copper layer is insufficient.
By introducing a palladium transition layer onto the carbon nanotube film and forming a copper layer thereon, electroplating is performed using an electrochemical reaction system to optimize the process parameters to improve the interface bonding force between the carbon nanotube and copper.
The specific conductivity and current carrying capacity of the metallized carbon nanotube film are significantly improved, and its mechanical properties, including tensile strength.
Smart Images

Figure CN115787008B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a metallized carbon nanotube film, in particular to a high-conductivity, high-strength metallized carbon nanotube film and a preparation method thereof, and belongs to the technical field of nanocomposite materials. Background Art
[0002] Carbon nanotube (CNT) film is a two-dimensional self-supporting material with a porous structure obtained by combining a large number of CNTs through van der Waals forces. It has the characteristics of light weight, flexibility, and good conductivity. As one of the macroscopic materials of CNT, the film has the same excellent properties as CNT. Due to the contact resistance between tubes, the conductivity of CNT film is only 10 4 S / m is far lower than the theoretical value of a single carbon nanotube. The orderly arrangement and densification of CNTs will greatly improve their conductivity. In addition, metallizing CNT films is the most direct and effective way to improve their conductivity.
[0003] Composite CNT and metal can be achieved through physical deposition, chemical deposition and electrodeposition. The composite metal will improve the conductivity of the CNT network. Hata used a two-step electrodeposition method to composite CNT film with copper (Subramaniam C, Yamada T, Kobashi K, et al. One hundred fold increase in current carrying capacity in a carbon nanotube-copper composite [J]. Nature Communications, 2013, 4 (August 2014): 1-7). First, the CNT film was immersed in an acetonitrile solution containing copper acetate to introduce it into copper, and then acidic copper was electrodeposited to obtain a conductivity of up to 4.7×10 7 S / m CNT / Cu composite film, and the current carrying capacity of the film is 100 times that of copper.
[0004] Wang et al. prepared a nanostructured carbon nanotube with a conductivity of up to 1.6×10 7S / m CNT / Cu composite films, and studied the effect of interface microstructure on the electrical properties of the film (Wang G, Sun C, Cai Y, et al. Improvement of interface and electrical properties in carbon nanotube / nanocrystalline copper composite films [J]. Materials Chemistry and Physics, 2018, 223 (June 2018): 374-379). The study shows that the composite film has such high conductivity mainly because two special interface structures are formed between CNT and Cu. The interface structure has low electron scattering to promote the formation of local ballistic conductors between CNT and Cu, thereby reducing the contact resistance between CNT and Cu. The carbon nanotube film prepared by the above method has a carbon nanotube layer and a copper layer interface separation, and copper is the main conductive structure, which loses the performance characteristics of the carbon nanotube film with light weight, and the specific conductivity (conductivity / density) of the final product is low.
[0005] In summary, the existing preparation methods of metallized carbon nanotube films have many disadvantages, for example, when the evaporation method is used, the carbon nanotube layer and the copper layer are relatively independent and the interface bonding force is poor. When the magnetron sputtering method is used, the carbon nanotube layer and the copper layer are relatively independent and the interface bonding force is strong. However, the specific conductivity is low and the mechanical strength is low. When the conventional electroplating method is used, the carbon nanotube layer and the copper layer are combined, and the interface bonding force is strong, but there are also defects such as low specific conductivity and low mechanical strength (poor interface bonding between copper and carbon nanotubes). Summary of the invention
[0006] The main purpose of the present invention is to provide a high-conductivity, high-strength metallized carbon nanotube film and a preparation method thereof, so as to overcome the deficiencies of the prior art.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0008] The embodiment of the present invention provides a method for preparing a high-conductivity and high-strength metallized carbon nanotube film, which comprises:
[0009] Providing pristine carbon nanotube films;
[0010] The carbon nanotube film is subjected to oxidation treatment, sensitization treatment and activation treatment in sequence, so as to form a palladium transition layer on the surface of the nanotube fibers contained in the original carbon nanotube film;
[0011] A copper layer is formed on a carbon nanotube film with a palladium transition layer to obtain a high-conductivity and high-strength metallized carbon nanotube film.
[0012] In some embodiments, the preparation method specifically comprises:
[0013] Provide plating solution;
[0014] The electrochemical reaction system including the carbon nanotube film with a palladium transition layer and the electroplating solution is electrified, the phosphor copper plate is used as the anode, and the carbon nanotube film with a palladium transition layer is used as the cathode, so as to electroplate on the carbon nanotube film with the palladium transition layer to deposit a copper layer, wherein the current density used in the electroplating is 50 to 300 A / m 2 The electroplating time is 5 to 30 minutes.
[0015] The embodiment of the present invention also provides a high-conductivity, high-strength metallized carbon nanotube film prepared by the above-mentioned preparation method, which includes a carbon nanotube film, and a palladium transition layer and a copper layer arranged on the surface of the nanotube fibers contained in the carbon nanotube film.
[0016] Compared with the prior art, the beneficial effects of the present invention are at least:
[0017] The method provided by the present invention introduces a palladium transition layer on the carbon nanotube film, and by continuously optimizing process parameters and formula regulation, the interface bonding between the carbon nanotubes and copper is further improved, and the contact resistance is effectively reduced. The prepared metallized carbon nanotube film has higher specific conductivity and specific current carrying capacity, and has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 This is a structural morphology diagram of a highly conductive, high-strength metallized carbon nanotube film obtained in a typical embodiment of the present invention. DETAILED DESCRIPTION
[0020] In view of the shortcomings of the traditional technical solutions, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly introduces a palladium transition layer on the conventional copper electroplating solution of carbon nanotube film. The technical solution, its implementation process and principle are further explained as follows.
[0021] One aspect of an embodiment of the present invention provides a method for preparing a highly conductive and high-strength metallized carbon nanotube film, comprising:
[0022] Providing pristine carbon nanotube films;
[0023] The carbon nanotube film is subjected to oxidation treatment, sensitization treatment and activation treatment in sequence, so as to form a palladium transition layer on the surface of the nanotube fibers contained in the original carbon nanotube film;
[0024] A copper layer is formed on a carbon nanotube film with a palladium transition layer to obtain a high-conductivity and high-strength metallized carbon nanotube film.
[0025] In some embodiments, the oxidant used in the oxidation treatment includes any one or a combination of two or more of concentrated sulfuric acid (98%), concentrated nitric acid (68%), hydrogen peroxide solution (30%), potassium permanganate (99.5%), etc., but is not limited thereto.
[0026] Furthermore, the oxidant may preferably be a combination of concentrated sulfuric acid and concentrated nitric acid, wherein the optimal ratio is 98% concentrated sulfuric acid and 68% concentrated nitric acid mixed in a volume ratio of 1 to 5:1.
[0027] In some embodiments, the oxidation treatment time is 1 to 2 hours.
[0028] In some embodiments, the preparation method further comprises: before the oxidation treatment, purifying the original carbon nanotube film to remove amorphous carbon.
[0029] Furthermore, the method for removing amorphous carbon (i.e., purification treatment) of the present invention can be carried out by any method such as tube furnace heating, electric heating, etc. Among them, when using tube furnace heating, the temperature can be heated to 200-500°C, and the heating and heat preservation time is 2-6 hours. When electric heating is used, a thermocouple or infrared thermal imager can be used for observation, and the power is continuously increased until the temperature reaches 200-500°C, and the constant power is maintained for 1-5 hours.
[0030] In some embodiments, the original carbon nanotube film is prepared by a floating catalytic method and has a thickness of 10 to 20 microns.
[0031] In some embodiments, the preparation method comprises: placing the oxidized carbon nanotube film in a sensitizer, and performing a sensitization treatment under ultrasound for 10 to 30 minutes.
[0032] Furthermore, the sensitizer includes a mixture of tin salt, HCl, tin particles and water. The concentration of the tin salt in the sensitizer is 20-50 g / L, the concentration of HCl is 1-6 ml / L, and the concentration of the tin particles is 0.1-2 g / L. For example, the tin salt can be SnCl2.
[0033] In some embodiments, the preparation method comprises: placing the sensitized carbon nanotube film in an activator, and performing an activation treatment under ultrasound for 2 to 15 minutes.
[0034] Further, the activator comprises a mixture of palladium salt, HCl and water. More specifically, the concentration of palladium salt in the activator is 0.1-0.2 g / L, and the concentration of HCl is 1-12 ml / L. For example, the palladium salt can be PdCl2.
[0035] In some embodiments, the copper plating step in the preparation method may specifically include:
[0036] Provide plating solution;
[0037] The electrochemical reaction system including the carbon nanotube film with a palladium transition layer and the electroplating solution is electrified, the phosphor copper plate is used as the anode, and the carbon nanotube film with a palladium transition layer is used as the cathode, so as to electroplate on the carbon nanotube film with a palladium transition layer to deposit a copper layer, and finally prepare a high-conductivity, high-strength metallized carbon nanotube film with a structure of carbon nanotube-palladium-copper. The current density used in the electroplating is 50 to 300A / m 2 The electroplating time is 5 to 30 minutes.
[0038] In some embodiments, the plating solution includes a mixture of copper salt, H2SO4, HCl, and polyethylene glycol (PEG).
[0039] Furthermore, the concentration of the copper salt in the electroplating solution is 50-200 g / L, the concentration of H2SO4 is 20-100 g / L, the concentration of HCl is 12-30 ml / L, and the concentration of polyethylene glycol is 0.1-2 g / L. For example, the copper salt may be CuSO4.
[0040] Another aspect of the present invention is to provide a high-conductivity, high-strength metallized carbon nanotube film prepared by the above-mentioned preparation method, wherein the high-conductivity, high-strength metallized carbon nanotube film comprises a carbon nanotube film, and a palladium transition layer and a copper layer disposed on the surface of the nanotube fibers contained in the carbon nanotube film.
[0041] Furthermore, the conductivity of the high-conductivity, high-strength metallized carbon nanotube film is 0.5 to 2.7*10 7 S / m, specific conductivity is 12~20S·m 2 / g, current carrying capacity is 1~3*10 4 A / cm 2 , specific current carrying capacity is 0.5~1.5*10 4 A·cm / g, tensile strength is 300~400MPa.
[0042] In the above technical scheme, the present invention introduces a palladium transition layer on the conventional carbon nanotube film electroplating copper scheme, and further improves the interface bonding between carbon nanotubes and copper by continuously optimizing process parameters and formula regulation, effectively reducing the contact resistance. The prepared metallized carbon nanotube film has higher specific conductivity and specific current carrying capacity, and has excellent mechanical properties.
[0043] Compared with transition layers such as nickel and tin, the palladium transition layer is more tightly bonded to the carbon nanotubes and has smaller grains. It can improve the interface between carbon nanotubes and copper at a lower addition amount, effectively improving the electrical and mechanical properties of the metallized composite film. The conductivity of the prepared metallized carbon nanotube film is slightly lower than that of copper, and its specific conductivity and specific current carrying capacity are higher than those of copper and other metallized composite carbon nanotube films.
[0044] The present invention will be more fully understood through the following detailed description, which should be read in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are only exemplary of the present invention, which can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis of the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in virtually any appropriate detailed embodiment.
[0045] Example 1
[0046] This embodiment uses a carbon nanotube film prepared by a floating catalytic method as a raw material, and selects a carbon nanotube film with a thickness of 15 microns. The specific steps for preparing a high-conductivity, high-strength metallized carbon nanotube film are as follows:
[0047] Step 1: Purification
[0048] To remove amorphous carbon in the carbon nanotube film, in this embodiment, electric heating is used to remove amorphous carbon:
[0049] Use a thermocouple or infrared thermal imager to observe, continuously increase the power until the temperature reaches 400°C, and maintain the power constant for 2 hours to complete the purification operation.
[0050] Step 2: Oxidation
[0051] 98% concentrated sulfuric acid and 68% concentrated nitric acid were mixed in a volume ratio of 3:1 as an oxidant, and the oxidation treatment was performed for 2 hours.
[0052] Step 3: Palladium Plating
[0053] Sensitizer ratio:
[0054] SnCl2 30g / L
[0055] HCl 6ml / L
[0056] Tin particles 0.5g / L
[0057] Dissolve in aqueous solution and prepare in a volumetric flask.
[0058] The oxidized carbon nanotube film was placed in a sensitizer and subjected to sensitization treatment for 10 minutes under ultrasonic action.
[0059] Activator formula:
[0060] PdCl2 0.12g / L
[0061] HCl 12ml / L
[0062] Dissolve in aqueous solution and prepare in a volumetric flask.
[0063] The sensitized carbon nanotube film was placed in an activator and activated under ultrasonic treatment for 5 minutes.
[0064] Step 4: Copper Plating
[0065] Plating solution ratio:
[0066]
[0067] Set the current density to 100A / m 2 , the electroplating time is 15min.
[0068] Finally, a highly conductive and high-strength metallized carbon nanotube film with a structure of carbon nanotube-palladium-copper was prepared.
[0069] The structural morphology of the metallized carbon nanotube film prepared by this method is shown in FIG. Figure 1 As shown, the conductivity is 2.7*10 7 S / m, specific conductivity is 18S·m 2 / g, the current carrying capacity is 2.31*10 4 A / cm 2 , the specific current carrying capacity is 1.5*10 4 A·cm / g, and the tensile strength is 367MPa.
[0070] Example 2
[0071] This embodiment uses a carbon nanotube film prepared by a floating catalytic method as a raw material, and selects a carbon nanotube film with a thickness of 10 microns. The specific steps for preparing a high-conductivity, high-strength metallized carbon nanotube film are as follows:
[0072] Step 1: Purification
[0073] To remove amorphous carbon in the carbon nanotube film, a tube furnace is used to heat the amorphous carbon in this embodiment. The temperature of the tube furnace is 200° C. and the heating time is 6 hours:
[0074] Step 2: Oxidation
[0075] 98% concentrated sulfuric acid and 68% concentrated nitric acid were mixed in a volume ratio of 5:1 as an oxidant, and the oxidation treatment was performed for 1 hour.
[0076] Step 3: Palladium Plating
[0077] Sensitizer ratio:
[0078] SnCl2 20g / L
[0079] HCl 3ml / L
[0080] Tin particles 0.1g / L
[0081] Dissolve in aqueous solution and prepare in a volumetric flask.
[0082] The oxidized carbon nanotube film was placed in a sensitizer and subjected to sensitization treatment for 20 minutes under ultrasonic action.
[0083] Activator formula:
[0084] PdCl2 0.1g / L
[0085] HCl 10ml / L
[0086] Dissolve in aqueous solution and prepare in a volumetric flask.
[0087] The sensitized carbon nanotube film was placed in an activator and activated for 2 minutes under ultrasonic action.
[0088] Step 4: Copper Plating
[0089] Plating solution ratio:
[0090]
[0091] Set the current density to 300A / m 2 , the electroplating time is 5min.
[0092] Finally, a highly conductive and high-strength metallized carbon nanotube film with a structure of carbon nanotube-palladium-copper was prepared.
[0093] The conductivity of the metallized carbon nanotube film prepared by this method is 2.4*10 7 S / m, specific conductivity is 18S·m 2 / g, current carrying capacity is 2.1*10 4 A / cm 2, the specific current carrying capacity is 1.2*10 4 A·cm / g, and the tensile strength is 397MPa.
[0094] Example 3
[0095] This embodiment uses a carbon nanotube film prepared by a floating catalytic method as a raw material, and selects a carbon nanotube film with a thickness of 20 microns. The specific steps for preparing a high-conductivity, high-strength metallized carbon nanotube film are as follows:
[0096] Step 1: Purification
[0097] To remove amorphous carbon in the carbon nanotube film, in this embodiment, electric heating is used to remove amorphous carbon:
[0098] Use a thermocouple or infrared thermal imager to observe, continuously increase the power until the temperature reaches 500°C, and maintain the power constant for 1 hour to complete the purification operation.
[0099] Step 2: Oxidation
[0100] 98% concentrated sulfuric acid and 68% concentrated nitric acid were mixed in a volume ratio of 1:1 as an oxidant, and the oxidation treatment was performed for 2 hours.
[0101] Step 3: Palladium Plating
[0102] Sensitizer ratio:
[0103] SnCl2 50g / L
[0104] HCl 1ml / L
[0105] Tin particles 2g / L
[0106] Dissolve in aqueous solution and prepare in a volumetric flask.
[0107] The oxidized carbon nanotube film was placed in a sensitizer and subjected to sensitization treatment for 30 minutes under ultrasonic action.
[0108] Activator formula:
[0109] PdCl2 0.2g / L
[0110] HCl 1ml / L
[0111] Dissolve in aqueous solution and prepare in a volumetric flask.
[0112] The sensitized carbon nanotube film was placed in an activator and activated for 15 minutes under ultrasonic action.
[0113] Step 4: Copper Plating
[0114] Plating solution ratio:
[0115]
[0116]
[0117] Set the current density to 50A / m 2 , the electroplating time is 30min.
[0118] Finally, a highly conductive and high-strength metallized carbon nanotube film with a structure of carbon nanotube-palladium-copper was prepared.
[0119] The conductivity of the metallized carbon nanotube film prepared by this method is 2.8*10 7 S / m, specific conductivity is 20S·m 2 / g, the current carrying capacity is 2.44*10 4 A / cm 2 , the specific current carrying capacity is 1.6*10 4 A·cm / g, and tensile strength is 321MPa.
[0120] Example 4
[0121] The present embodiment is different from the embodiment 1 in that the power is turned on until the temperature reaches 200° C. and the power is kept constant for 5 hours.
[0122] The conductivity of the metallized carbon nanotube film prepared by this method is 2.8*10 7 S / m, specific conductivity is 20S·m 2 / g, the current carrying capacity is 2.44*10 4 A / cm 2 , the specific current carrying capacity is 1.6*10 4 A·cm / g, and tensile strength is 321MPa.
[0123] Example 5
[0124] The present embodiment is different from the embodiment 2 in that the heating temperature of the tube furnace is 500° C. and the heating time is 2 h.
[0125] The conductivity of the metallized carbon nanotube film prepared by this method is 2.4*10 7 S / m, specific conductivity is 18S·m 2 / g, current carrying capacity is 2.2*10 4 A / cm 2 , the specific current carrying capacity is 1.2*10 4 A·cm / g, and tensile strength is 302MPa.
[0126] Comparative Example 1
[0127] Compared with Example 1, this comparative example does not include step 3: palladium plating.
[0128] The conductivity of the carbon nanotube film prepared by this method is measured to be 3.1*10 7 S / m, specific conductivity is 14S·m 2 / g, current carrying capacity is 0.32*10 4 A / cm 2 , the specific current carrying capacity is 0.44*10 4 A·cm / g, and tensile strength is 121MPa.
[0129] Comparative Example 2
[0130] Compared with Example 1, in step 1: during purification, the electric heating temperature reaches 600 degrees.
[0131] During the electric heating process, the carbon nanotube film breaks under high-temperature oxidation conditions and subsequent processes cannot be carried out.
[0132] Comparative Example 3
[0133] Compared with Example 1, this comparative example does not include step 2: oxidation.
[0134] The conductivity of the carbon nanotube film prepared by this method is measured to be 0.4*10 7 S / m, specific conductivity is 12S·m 2 / g, current carrying capacity is 0.4*10 4 A / cm 2 , the specific current carrying capacity is 0.9*10 4 A·cm / g, and tensile strength is 155MPa.
[0135] Comparative Example 4
[0136] Compared with Example 1, this control example does not include step 1: purification.
[0137] The conductivity of the carbon nanotube film prepared by this method is measured to be 1.1*10 7 S / m, specific conductivity is 14S·m 2 / g, the current carrying capacity is 1.21*10 4 A / cm 2 , the specific current carrying capacity is 0.97*10 4 A·cm / g, and the tensile strength is 189MPa.
[0138] Comparative Example 5
[0139] Compared with Example 1, in step 4, during copper plating, the current density is 500A / m 2 , time 10 minutes.
[0140] Under this process condition, the copper layer on the surface of the carbon nanotube film is significantly enriched, and the flatness and uniformity are reduced.
[0141] The conductivity of the metallized carbon nanotube film prepared by this method is measured to be 4.5*10 7 S / m, specific conductivity is 11S·m 2 / g, the current carrying capacity is 0.87*10 4 A / cm 2 , the specific current carrying capacity is 0.54*10 4 A·cm / g, and the tensile strength is 241MPa.
[0142] Comparative Example 6
[0143] Compared with Example 1, in step 4, during copper plating, the current density is 100 A / m 2 , time 2 minutes.
[0144] Under this process condition, the copper content on the surface of the carbon nanotube film is relatively low, and the copper layer is missing in some areas.
[0145] The conductivity of the metallized carbon nanotube film prepared by this method is measured to be 0.12*10 7 S / m, specific conductivity is 6S·m 2 / g, current carrying capacity is 0.12*10 4 A / cm 2 , the specific current carrying capacity is 0.31*10 4 A·cm / g, and the tensile strength is 76MPa.
[0146] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0147] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A method for preparing a high-conductivity, high-strength metallized carbon nanotube film, characterized in that: include: Providing pristine carbon nanotube films; The carbon nanotube film is subjected to purification treatment, oxidation treatment, sensitization treatment and activation treatment in sequence, so as to form a palladium transition layer on the surface of the nanotube fibers contained in the original carbon nanotube film; the purification treatment adopts any one of tubular furnace heating and electric heating, the tubular furnace heating temperature is 200-500°C, the time is 2-6h, the electric heating temperature is 200-500°C, the time is 1-5h; the oxidation treatment time is 1-2h; the sensitization treatment time is 10-30min, and the sensitizer used in the sensitization treatment is selected from a mixture of tin salt, HCl, tin particles and water; the activation treatment time is 2-15min, and the activator used in the activation treatment is selected from a mixture of palladium salt, HCl and water; An electroplating solution is provided to energize an electrochemical reaction system including a carbon nanotube film with a palladium transition layer and an electroplating solution, a phosphor copper plate is used as an anode, and a carbon nanotube film with a palladium transition layer is used as a cathode, thereby electroplating is performed on the carbon nanotube film with a palladium transition layer to deposit a copper layer, and a high-conductivity, high-strength metallized carbon nanotube film is obtained; wherein the current density used in the electroplating is 50 to 300 A / m 2 , the electroplating time is 5 to 30 minutes; The high-conductivity, high-strength metallized carbon nanotube film comprises a carbon nanotube film, and a palladium transition layer and a copper layer arranged on the surface of nanotube fibers contained in the carbon nanotube film; wherein the electrical conductivity of the high-conductivity, high-strength metallized carbon nanotube film is 0.5 to 2.7*10 7 S / m, specific conductivity is 12~20S·m 2 / g, current carrying capacity is 1~3*10 4 A / cm 2 , specific current carrying capacity is 0.5~1.5*10 4 A·cm / g, tensile strength is 300~400MPa.
2. The preparation method according to claim 1, characterized in that: The oxidant used in the oxidation treatment is selected from any one of concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide solution, and potassium permanganate, or a combination of two or more thereof.
3. The preparation method according to claim 2, characterized in that: The oxidant used in the oxidation treatment is selected from a combination of concentrated sulfuric acid and concentrated nitric acid.
4. The preparation method according to claim 3, characterized in that: The volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1 to 5:
1.
5. The preparation method according to claim 1, characterized in that: include: The oxidized carbon nanotube film is placed in a sensitizer and subjected to sensitization treatment under ultrasonic action.
6. The preparation method according to claim 5, characterized in that: The concentration of the tin salt in the sensitizer is 20-50 g / L, the concentration of HCl is 1-6 ml / L, and the concentration of the tin particles is 0.1-2 g / L.
7. The preparation method according to claim 5, characterized in that: include: The sensitized carbon nanotube film is placed in an activating agent and activated under ultrasonic action.
8. The preparation method according to claim 7, characterized in that: The concentration of palladium salt in the activator is 0.1-0.2 g / L, and the concentration of HCl is 1-12 ml / L.
9. The preparation method according to claim 1, characterized in that: The electroplating solution is selected from a mixture of copper salt, H2SO4, HCl and polyethylene glycol.
10. The preparation method according to claim 9, characterized in that: The concentration of copper salt in the electroplating solution is 50-200 g / L, the concentration of H2SO4 is 20-100 g / L, the concentration of HCl is 12-30 ml / L, and the concentration of polyethylene glycol is 0.1-2 g / L.
11. The preparation method according to claim 1, characterized in that: Also includes: Before the oxidation treatment, the original carbon nanotube film is purified to remove amorphous carbon.
12. The preparation method according to claim 1, characterized in that: Also includes: The original carbon nanotube film is prepared by a floating catalytic method and has a thickness of 10 to 20 μm.
13. A high-conductivity, high-strength metallized carbon nanotube film prepared by the preparation method according to any one of claims 1 to 12.
Citation Information
Patent Citations
Method for metalizing surfaces of carbon nanotubes
CN104593753A
Method for chemically plating copper on surface of carbon nano tube
CN114774898A
Carbon nanotube / copper composite material and preparation method thereof
CN115305532A